DAMPAK ANEMIA PADA IBU HAMIL DAN PERSALINAN - Stefani Anastasia Sitepu; Tetty Junita Purba; Nur Mala Sari; Marlen Sadrina Sitepu; Erlina Hayati (INSTITUT KESEHATAN DELI HUSADA, 2021)
Anemia is one of the health problems worldwide, especially developing countries that are estimated to be 30% of the world's population suffering from anemia. Anemia occurs in many people, especially in pregnant women. The risk of anemia in pregnant women is not playful, pregnant women who have anemia face the risk of death in pregnancy. Every year, there are 500 thousand deaths of postpartum mothers worldwide, as many as 20-40% of which are the leading cause of death is anemia. Anemia in pregnant women who are not treated properly can increase the risk of dangerous complications, such as preterm labor. In addition, anemia can also increase the risk of low birth weight in babies. On the mother's side, anemia can increase the risk of postpartum depression and postnatal maternal death.